2009
DOI: 10.1002/chem.200900397
|View full text |Cite
|
Sign up to set email alerts
|

Lys314 is a Nucleophile in Non‐Classical Reactions of Orotidine‐5′‐Monophosphate Decarboxylase

Abstract: Orotidine-5'-monophosphate decarboxylase (OMPD) catalyzes the decarboxylation of orotidine-5'-monophosphate (OMP) to uridine-5'-monophosphate (UMP) in an extremely proficient manner. The reaction does not require any cofactors and proceeds by an unknown mechanism. In addition to decarboxylation, OMPD is able to catalyze other reactions. We show that several C6-substituted UMP derivatives undergo hydrolysis or substitution reactions that depend on a lysine residue (Lys314) in the OMPD active site. 6-Cyano-UMP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…Although the distortion is not very obvious in the present ester complexes due to overlapping electron densities, the bonds linking the C6 atoms and the respective substituents of 6-methyl-UMP, 6-cyano-UMP and 6-acetyl-UMP are clearly distorted in their ODCase complexes (Fig 2A and refs. 15,20 ). In addition, our WT-UMP complex structure, recently determined at atomic resolution (1.03 Å), indicates that the pyrimidine ring of UMP itself is slightly distorted, too.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the distortion is not very obvious in the present ester complexes due to overlapping electron densities, the bonds linking the C6 atoms and the respective substituents of 6-methyl-UMP, 6-cyano-UMP and 6-acetyl-UMP are clearly distorted in their ODCase complexes (Fig 2A and refs. 15,20 ). In addition, our WT-UMP complex structure, recently determined at atomic resolution (1.03 Å), indicates that the pyrimidine ring of UMP itself is slightly distorted, too.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Similarly distorted ligands were found in the structures of several compounds bound to human-ODCase ( Hs ODCase) 19,20 and it has been suggested that the size of the C6-substituents of the pyrimidine ring is the dominant factor in determining the extent of the observed deviation from low energy conformations. 20 As the stable existence of such distorted structures strongly argues for the involvement of substrate distortion in ODCase catalysis we engaged in further analysis and investigated the crystal structures of four more complexes, i.e. the structures of 6-methyl-UMP, 6-amino-UMP, OMP-methyl-ester, and OMP-ethyl-ester (Fig.…”
Section: Introductionmentioning
confidence: 98%
“…Such a distortion effect was observed in crystal structures of various ODCase-ligand complexes, such as OMP, 6-aceto-UMP, and 6-cyano-UMP, with both MtODCase and human ODCase (11)(12)(13)(14). For 6-cyano-UMP, such a distortion receives strong support from Raman spectroscopy, which indicates bond bending of about 20° (15).…”
mentioning
confidence: 78%
“…The loss of entropy also affects nucleotide analogues that inhibit ODC, which likely explains why inhibition constants are all in the high micromolar range (except for those inhibitors that bind covalently to the enzyme, e.g. 6-iodo-UMP) (26).…”
Section: Discussionmentioning
confidence: 99%
“…It also has a hydrogen bond donor (amino group) at C4 analogous to the phenolic hydroxyl group at C4 of 3F-3DUrd. It is possible that 3F-3DUrd binds to human ODC by occupying its active site in a different manner than other potent inhibitors such as 5Ј-phosphoribofuranosyl barbituric acid and 6AUrd that are anchored through an extended hydrogen-bonded network involving all of the phosphate oxygens, the ribose hydroxyl groups, and the nucleobase (26).…”
Section: Discussionmentioning
confidence: 99%